Oral health and related quality of life status in patients from UK and Turkey: a comparative study in Behcet's disease - MUMCU, GONCA; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (WILEY, 2009)
The aim of this study was to evaluate and compare oral health-related quality of life (oral QoL) in patients from UK and Turkey with Behcet's disease (BD). Thirty-one BD patients from UK (F/M: 18/13, mean age: 41.8 +/- 11.5 years) and Turkey (F/M: 18/13, mean age: 41.5 +/- 10.3) who were matched according to age and gender were included in the study. All patients had active oral ulcers. Oral QoL was assessed by Oral Health Impact Profile-14 (OHIP-14). Oral health was evaluated by dental and periodontal indices. No significant difference was found in OHIP-14 scores between patients from UK (22.7 +/- 14.4) and Turkey (20.4 +/- 14.3) (P = 0.709). The OHIP-14 score correlated with the healing time of oral ulcers in UK (r = 0.4, P = 0.04) and the number of oral ulcers in Turkey (r = 0.4, P = 0.012). The number of oral ulcers per month was significantly higher in UK (3.3 +/- 2.8) compared with that in Turkey (1.5 +/- 2.5) (P = 0.014). However, the number of filled teeth and frequency of tooth brushing were significantly lower in patients from Turkey compared with those in UK (P = 0.000). Similarly, the duration since the last dental visit (5.1 +/- 7.2 months) was significantly lower in UK compared with that in Turkey (28.6 +/- 23.7 months) (P = 0.000). Oral QoL was similar in patients from UK and Turkey with active oral ulcers. However, the number of oral ulcers was observed to be higher in UK. As expected, a lower utilization rate of dental services might have led to a poorer oral health in patients from Turkey.
Keywords: Behcet's disease; OHIP-14; oral health; quality of life; Turkey; UK; TURKISH; IMPACT; ORIGIN